A case report of rectal schwannoma treated with laparoscopic proctectomy. Issue 7 (February 2018) - Zhang, Kai; Qu, Shanshan; Li, Junan; Cheng, Ye; Shi, Jian; Liu, Tongjun
Abstract: Rationale: Schwannomas of gastrointestinal tracts are rare and difficult to detect preoperatively because of negative results of endoscopic and imaging examinations. Here, we reported a case of rectal schwannoma, which was diagnosed by immunohistochemical staining after laparoscopic protectomy. Patient concerns: A 61-year-old woman complained of a 1-month history of difficulty in defecation and irregularly abdominal discomfort during her physical checkup in our hospital. Diagnoses: Immunohistochemical staining results after laparoscopic protectomy revealed a strong positive reaction for S-100 protein. Therefore, rectal schwannoma was confirmed. Interventions: Treatment with laparoscopic protectomy was given. Outcomes: Symptoms resolved completely after 12 days of the surgery, and was regular followed-up in outpatient clinic. Lessons: Schwannomas are difficult to identify preoperatively, and immunohistochemical staining for S-100 protein is an effective method to diagnose it.